Colloboratively creating a thematic repository using interactive table-top technology - Zaphiris, Panayiotis; Vasiliou, Ioannou; Ioannou, Andri; Loizides, Fernando (My University, 2012)
This paper reports on the design and development of a surface computing application in support of collaborative idea creation and thematic categorisation. C.A.R.T (Collaborative Assisted Repository for Tabletops) allows up to 4 users to simultaneously interact with virtual objects, each containing a single concept, to create thematic categories. Each object, which replicates a physical post-it on a multi-touch tabletop, is created by one of the team members either previous to the meeting or during the initial stage. The application then encourages the exchange of debate and conversation by presenting the ideas one at a time for users to discuss and categorise. The resulting idea repository can be used for roadmap creation as well as comparative studies using further participants. The application’s main task is similar to that of card sorting and affinity diagramming. We report on the functionality of the application which was designed and developed following a user-centred approach.
Keywords: Tablet computers; Technology